Effects of the Peer-Review Method on Writing Proficiency - Čėsnienė, Žaneta (Pedagogika, 2015)
Although peer-review has proved to be beneficial in many writing classrooms abroad, this method is scarcely used among Lithuanian educators. Different studies highlight contrastive results, weighing either to the benefit of teacher-or peer-review. The value of peer-review is often underestimated because teachers tend to undervalue students’ abilities as both writers and reviewers. To achieve the most from peer-review, it is important to define the actual expectations for peer-review and to form an appropriate peer-editing rubric as a helpful tool for peer-reviewers. Different analyses of peer-reviewed and self-reviewed writings highlighted the differences between peer-reviewers’ and self-reviewers’ ability to notice errors, revise, and improve writings. The article inquires into the peer-review method as a way to promote students’ writing proficiency and describes the research conducted at Klaipėda University after having introduced the peer-review method in the study process. The research describes quantitative and qualitative research results based on peer-reviews, self-reflections and questionnaires filled in by the 1st year English Philology students. The research results prove that the peer-review method helps to develop critical evaluation skills, equipping students with the ability to effectively review and notice various defects that weaken the argument of the paper on a local as well as global level, thus making students better writers. The peer-review method activates cognitive processes that influence learning, as students get actively involved into the learning process facilitating their peers and improving their own writing skills. Peer-review modeling in the classroom develops not only students’ specific but also personal and social skills and leads to students’ constructive collaboration by shifting from the teacher-centered to student-centered learning approach.